Effect of photobiomodulation in the balance between effector and regulatory T cells in an experimental model of COPD - Brito, Auriléia Aparecida de; Herculano, Karine Zanella; de Alvarenga-Nascimento, Cristiano Rodrigo; Estefano-Alves, Cintia; Duran, Cinthya Cosme Gutierrez; Marcos, Rodrigo Labat; Silva Junior, José Antonio; Chavantes, Maria Cristina; Zamuner, Stella Regina; Aimbire, Flávio; Lladó-Pelfort, Laia; Gubern, Albert; et al. (Frontiers in Medicine, 2024)
Currently, Chronic Obstructive Pulmonary Disease (COPD) has a high impact on morbidity and mortality worldwide. The increase of CD4+, CD8+ cells expressing NF-κB, STAT4, IFN-𝛄 and perforin are related to smoking habit, smoking history, airflow rate, obstruction and pulmonary emphysema. Furthermore, a deficiency in CD4+CD25+Foxp3+ regulatory T cells (Tregs) may impair the normal function of the immune system and lead to respiratory immune disease. On the other hand, the anti-inflammatory cytokine IL-10, produced by Treg cells and macrophages, inhibits the synthesis of several pro-inflammatory cytokines that are expressed in COPD. Therefore, immunotherapeutic strategies, such as Photobiomodulation (PBM), aim to regulate the levels of cytokines, chemokines and transcription factors in COPD. Consequently, the objective of this study was to evaluate CD4+STAT4 and CD4+CD25+Foxp3+ cells as well as the production of CD4+IFN- 𝛄 and CD4+CD25+IL-10 in the lung after PBM therapy in a COPD mice model. We induced COPD in C57BL/6 mice through an orotracheal application of cigarette smoke extract. PMB treatment was applied for the entire seven weeks and Bronchoalveolar lavage (BAL) and lungs were collected to study production of IFN- 𝛄 and IL-10 in the lung. After the last administration with cigarette smoke extract (end of 7 weeks), 24 hours later, the animals were euthanized. One-way ANOVA followed by NewmanKeuls test were used for statistical analysis with significance levels adjusted to 5% (p<0.05). Results showed that PBM improves COPD symptomatology, reducing the number of inflammatory cells (macrophages, neutrophils and lymphocytes) ,the levels of IFN-γ among others, and increased IL-10. We also observed a decrease of collagen, mucus, bronchoconstriction index, alveolar enlargement, CD4+, CD8+, CD4+STAT4+ and CD4+IFN-γ+ cells. In addition, in the treated group, we found an increase in CD4+CD25+Foxp3+ and CD4+IL-10+ T cells. This study suggests that PBM treatment could be applied as an immunotherapeutic strategy for COPD,